Barriers of food delivery applications: A perspective from innovation resistance theory using mixed method. (July 2023) - Verma, Anuj; Chakraborty, Debarun; Verma, Meenakshi
Abstract: Introduction: Food delivery applications (FDAs) have altered the way customers order and consume food. This was compounded by the COVID-19 pandemic, which imposed restrictions on people's mobility. In this study, the authors have tried to determine which barriers affect consumers' emotions and feelings, leading to satisfaction, repeat visit, and WOM recommendations. Method: ology: The Innovation Resistance Theory has been used to conduct the study. The Mixed Model is also framed to address the barriers faced by FDA users. This study also identifies key barriers of FDA (Value Barrier, Image Barrier, and Environment Barrier) and also studies their effect on consumer emotions and feelings in addition to the impact on repeat purchase behaviour, customer satisfaction and word of mouth recommendation. The data is collected from 392 respondents. Findings: The findings demonstrate that apart from the value barrier, all the other barriers have negative and significant impacts on consumers' feelings and emotions. It further supports the mediation effect amongst consumer feelings and emotions, satisfaction, repeat purchase, and WOM recommended. The moderating effect of transaction cost has been shown with different associations. Implications: The service providers should make sure that all transactions are safe and secure and that food is delivered on time. They should also have good ways for customers to get in touch with them, so they will get orders from them. Originality: The focus of the study is on the link between satisfaction, repeat purchases, and word-of-mouth recommendations for FDA, which hasn't been looked into in any previous studies.